Two new aphid species from Campanulaceae in Italy (Homoptera Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Dysaphis (Pomaphis) henrystroyani sp. n. and Uroleucon (Uromelan) minosmartellii sp. n. are described from ltaly where they live on Campanulaceae of the genera Trachelium and Campanula, respectively. For each one of the two taxa accounts are given on both apterous and alate viviparous morphs, their host plants, ethology and taxonomy; a key to separate the two new taxa from the other similar species living on Campanulaceae in W-Europe is also included.
Keywords: Homoptera Aphididae; Dysaphis (Pomaphis) henrystroyani sp. n.; Uroleucon (Uromelan) minosmartellii sp. n.; Campanulaceae-living aphids; Italy